Design of a modified atmosphere storage system for shelf life enhancement of mango (Mangifera indica, cv. Amrapali). Issue 9 (19th April 2022) - Thakur, Rajeev Ranjan; Mangaraj, Shukadev; Tripathi, Manoj Kumar; Singh, Krishna Pratap; Jadhav, Mahesh Laxman
Abstract: Modified atmosphere storage (MAS) system was developed under passive as well as active conditions for bulk handling and storage of mango. The developed mathematical model used in the design process was validated and found to be appropriate, as indicated by moduli ( E  < 10%). The use of O2 absorber in the active MAS system has extended the shelf life of mango by 3.5 times as compared to control along with maintaining good quality attributes at the end of the storage period at ambient temperature (27°C). It may be due to attainment of an early dynamic equilibrium O2 and CO2 concentrations which were much close to the targeted level. The shelf life of mango under control, passive and active condition was found to be 4, 10 and 14 days, respectively. The extra shelf life gained by mango under active MAS condition may provide buffer period for storage, retailing and distribution during supply chain. Novelty impact statement: The main cause of post‐harvest loss of crop like mango and other fresh produce is the poor handling due to unavailability of a bulk storage system at on‐farm level. Therefore, it is essential to develop an economical storage system which can facilitate large quantity storage of mango to the farmers at their orchard level itself. Hence, in the above context, our study is an attempt made to develop, design and compare an active as well as passive MAS system for mango. These uniquely developed and designed MAS systems were evaluated under passive as well as active condition by storing 100 kg of mango inside them. From the results, it was quite clear that an active MAS system can provide long‐term storage of mango even at on‐farm storage condition and can also facilitate a buffer period to the farmers during retailing and distribution.